Modeling and development of screen-printed impedance biosensor for cytotoxicity studies of lung carcinoma cells - Mohd Mansor, Ahmad Fairuzabadi; Ibrahim, Irmanisha; Zainuddin, Ahmad Anwar; Voiculescu, Ioana; Nordin, Anis Nurashikin (Springer, 2018)
Electrical cell-substrate impedance sensing (ECIS) is a powerful technique to monitor real-time cell behavior. In this study, an ECIS biosensor formed using two interdigitated electrode structures (IDEs) was used to monitor cell behavior and its response to toxicants. Three different sensors with varied electrode spacing were first modeled using COMSOL Multiphysics and then fabricated and tested. The silver/silver chloride IDEs were fabricated using a screenprinting technique and incorporated with polydimethylsiloxane (PDMS) cell culture wells. To study the effectiveness of the biosensor, A549 lung carcinoma cells were seeded in the culture wells together with collagen as an extracellular matrix (ECM) to promote cell attachment on electrodes. A549 cells were cultured in the chambers and impedance measurements were taken at 12-h intervals for 120 h. Cell index (CI) for both designs were calculated from the impedance measurement and plotted in comparison with the growth profile of the cells in T-flasks. To verify that the ECIS biosensor can also be used to study cell response to toxicants, the A549 cells were also treated with anti-cancer drug, paclitaxel, and its responses were monitored over 5 days. Both simulation and experimental results show better sensitivity for smaller spacing between electrodes.